A nodular growth on maxillary gingiva - Amita Aditya; Shailesh Lele (Wolters Kluwer Medknow Publications, 2012)
A case of angiosarcoma of maxilla is presented. The occurrence of angiosarcoma in the oral cavity is a rare incidence and maxilla is one of the rarest sites to be involved. The purpose of this article is also to emphasize the fact that sometimes small, innocent-looking masses in the oral cavity might actually turn out to be a highly destructive malignant tumor. Hence, a complete radiographic and histopathologic examination is mandatory.